OP0143 Genetic determinants of the th1 bias in rheumatoid arthritis. (1st June 2001) - Skapenko, A; Wendler, J; Mueller, R; Lipsky, PE; Kalden, JR; Schulze-Koops, H
Abstract : Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease, which is likely to be driven by activated pro-inflammatory Th1 cells. In contrast, Th2 cells and their cytokines, in particular IL-4 are rarely found in RA. It could recently be demonstrated that memory T cells from patients with early RA manifest a profound functional deficit in that they cannot differentiate into Th2 cells even at very early stages of the disease. The inability of memory T cells to mount immunomodulatory Th2 effectors might contribute to the Th1 bias in RA and, thus, might by critically involved in the initiation of chronic autoimmune inflammation. The mechanisms, however, involved in this abnormality have not been delineated in detail. We have recently established a system to analyse T cell differentiation in vitro and have identified molecular mechanisms regulating Th2 effector generation in healthy individuals. In the current proposal, molecular mechanisms will be identified that are involved in the development of Th1 mediated immunity in patients with very early rheumatoid arthritis (symptoms at time of blood collection of ≤2 weeks) using gene chip microarray technology. Selected candidate genes associated with the Th2 cell differentiation defect will be tested for their functional significance in biological assays. The definition of mechanisms contributing to the Th1 differentiation bias in very early RA will provide important insights into the pathogenesis of the disease, in particular into the initial steps of the evolving immune response, and might lead to the development of novel therapeutic strategies.